(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Hydrocephalus is usually associated with functional deficits which can be assessed by neurobehavioral tests. This study characterizes the neurobehavioral deficits occurring with increasing duration and severity of ventriculomegaly in an experimental neonatal hydrocephalic rat model. Hydrocephalus was induced in three weeks old albino rats by intracisternal injection of kaolin while controls received sterile water injection. They were sacrificed in batches at one, four and eight weeks post-injection after neurobehavioral tests (forelimb grip strength, open field and Morris water maze tests) were performed. The hydrocephalic rats were also categorized into mild, moderate and severe hydrocephalus based on ventricular size. The indices of muscular strength and vertical movements in severely hydrocephalic rats were 28.05 ± 5.19 seconds and 7.29 ± 2.71 rearings respectively, compared to controls (75.68 ± 8.58 seconds and 17.09 ± 1.25 rearings respectively). At eight weeks, vertical movements were significantly reduced in hydrocephalic rats compared to controls (3.14 ± 1.3 vs 13 ± 4.11 rearings). At one week, indices of learning and memory were significantly reduced in hydrocephalic rats, compared to controls (0.89±0.31 vs 3.88±1.01 crossings), but at 8 weeks, the indices were similar (2.56 ± 0.41 vs 3.33 ± 0.71 crossings). Untreated hydrocephalus is accompanied by decline in motor functions which increase with duration and severity of ventriculomegaly. However, cognitive deficits appear to partially recover.